2013
DOI: 10.1056/nejmoa1214479
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in DSTYK and Dominant Urinary Tract Malformations

Abstract: BACKGROUND Congenital abnormalities of the kidney and the urinary tract are the most common cause of pediatric kidney failure. These disorders are highly heterogeneous, and the etiologic factors are poorly understood. METHODS We performed genomewide linkage analysis and whole-exome sequencing in a family with an autosomal dominant form of congenital abnormalities of the kidney or urinary tract (seven affected family members). We also performed a sequence analysis in 311 unrelated patients, as well as histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
108
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 27 publications
(30 reference statements)
3
108
0
1
Order By: Relevance
“…With the exception of rare syndromic forms of CAKUT, the mutations underlying these familial forms are largely unknown (12). The three genes most commonly implicated in nonsyndromic forms of CAKUT are PAX2 (encoding for a nuclear transcription factor involved in early nephrogenesis), HNF1B (encoding for a transcription factor originally implicated in the renal cysts and diabetes syndrome [Online Mendelian Inheritance in Man 137920]), and DSTYK (encoding for a dual specificity serine/threonine and tyrosine kinase; recently identified as a positive regulator of fibroblast growth factor signaling during kidney development) (16). However, many other genes have been implicated in CAKUT phenotypes underlying a solitary functioning kidney (Table 1).…”
Section: Genetic Factorsmentioning
confidence: 99%
“…With the exception of rare syndromic forms of CAKUT, the mutations underlying these familial forms are largely unknown (12). The three genes most commonly implicated in nonsyndromic forms of CAKUT are PAX2 (encoding for a nuclear transcription factor involved in early nephrogenesis), HNF1B (encoding for a transcription factor originally implicated in the renal cysts and diabetes syndrome [Online Mendelian Inheritance in Man 137920]), and DSTYK (encoding for a dual specificity serine/threonine and tyrosine kinase; recently identified as a positive regulator of fibroblast growth factor signaling during kidney development) (16). However, many other genes have been implicated in CAKUT phenotypes underlying a solitary functioning kidney (Table 1).…”
Section: Genetic Factorsmentioning
confidence: 99%
“…14 Whole-exome sequencing was performed on individual 58 using an Illumina HiSeq 2000 as previously described. 15 …”
Section: Genotyping Mapping and Sequencingmentioning
confidence: 99%
“…13 The advent of next generation sequencing boosted gene discovery for Mendelian diseases and helped in solving the pathogenesis of numerous familial and sporadic genetic nephropathies. [14][15][16] Although this technology helped to formulate accurate diagnosis and improve knowledge in pathophysiological and therapeutic aspects of many diseases, there are increasing examples in which deep resequencing of human genomes or exomes showed that many genes can harbor mutations with pleiotropic phenotypic effect that confounded traditional gene identifi cation approaches. 17,18 In a recent report, Boyer et al 18 performed whole-exome sequencing in families with autosomal dominant FSGS without extrarenal manifestations to surprisingly identify segregating mutations in LMX1B, a gene implicated in the nail patella syndrome.…”
mentioning
confidence: 99%
“…5,6 Twentythree autosomal dominant genes have been identified to cause isolated CAKUT, with TNXB, WNT4, and DSTYK being the most recent ones. [7][8][9][10] According to the Mouse Genome Informatics database (http://www.informatics.jax.org), 1768 monogenic mouse models for CAKUT have been described, many of which are recessive and do not have a human disease correlate.…”
mentioning
confidence: 99%
“…These six genes contribute to 2.5% of all cases of isolated CAKUT; thus, up to 20% of individuals with CAKUT could now be molecularly "solved" by exon sequencing in 29 genes and copy number variation analysis. 9,[29][30][31] Rapidly developing sequencing technology will continue to facilitate identification of rare singlegene causes of human CAKUTand enables us to conduct large-scale mutation analyses providing families with a genetic diagnosis in an increasing number of cases.…”
mentioning
confidence: 99%